KOMPETENSI PEDAGOGIS GURU PLB DALAM MENINGKATKAN PRESTASI BELAJAR ANAK BERKEBUTUHAN KHUSUS - Irah Kasirah (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
This research aims at describing pedagogical competence of the special education teachers in improving the students’ learning achievement at the 5th grade in SLB N 5 Tanah Abang, Jakarta. Based on its objective, this research is descriptive covering 12 teachers and all students totaled 30 students. To know the data of the teachers’ pedagogical competence, PLPG tests were used and to know the students’ learning achievement, document study was done. The result of the research indicates both the teachers’ pedagogical competence and the students’ learning achievement can be categorized good with each of them 74.73% and 71.95 %.